The motorcycle diaries [videorecording (DVD)] - Salles, Walter; García Bernal, Gael, 1978-; Serna, Rodrigo de la, 1976-; Maestro, Mía; Guevara, Che, 1928-1967; Granado, Alberto, 1922-2011 (Universal, 2005)
An inspirational adventure, based on the true story of two young men whose thrilling and dangerous road trip across Latin America becomes a life-changing journey of self-discovery.